The blue revolution in Asia: Upgrading and governance in aquaculture value chains - Ponte, S.; Kelling, I.; Jespersen, K.S.; Kruijssen, Froukje (Elsevier, 2014)
In this article, we examine the upgrading trajectories of selected aquaculture value chains in four Asian countries and the links between upgrading and three factors of value chain governance: coordination mechanisms; types of drivers; and domestic regulation. We find instances of improving products, processes, and value chain coordination—while “moving up” the value chain is rare. We also find that the type of value chain driver and the quality of the domestic regulatory framework are main facilitators of upgrading. We conclude by highlighting lessons on the potential, limits and risks of upgrading the “blue revolution” in Asia.